American Global Challenges - Zaki, M. author. aut Link
XI, 198 p.
Keywords: Discussing the most pressing global challenges, this book suggests ways for the Obama Administration to tackle them in a holistic manner. In particular, the book proposes effective measures for various problems like the war on terror, resolution of the Arab-Israeli dispute, and forging of better relations with the Muslim World.